Analysis Of The Influence Of Spiritual Capital, Motivation And Work Competencies On Performance Of Human Resource In Smes Sector - Balla Wahyu Budiarto; Wulandari; Sugeng Karyadi; Loso Judijanto; Wenny Desty Febrian (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study uses competence as a moderating variable in SMEs to assess and evaluate the impact of motivation and spiritual capital on SME performance. Primary and secondary data, gathered from 100 respondents, were used in this study. Path analysis is used to process the data after the non-probability sampling methodology using purposive sampling method was used in this study. The study's findings suggest that, in structure I, spiritual capital and motivation play a major role in competence. Competency is not significantly impacted by motivation at the same time as it is by spiritual capital. The elements of competence, spiritual capital, and motivation have a big impact on success in structure II. The results of the Adjusted R Square analysis of the coefficient of determination (R2) in structure I show that the combined effect of spiritual capital and motivation is 75%, with other variables influencing the remaining. The results of the analysis of the coefficient of determination (R2) in structure II show an Adjusted R Square of 60%, indicating that other factors have an influence on the remaining 40% of the effect, which is the simultaneous influence of competence, spiritual capital, and motivation.